2018
DOI: 10.7150/thno.23491
|View full text |Cite
|
Sign up to set email alerts
|

Evans Blue Attachment Enhances Somatostatin Receptor Subtype-2 Imaging and Radiotherapy

Abstract: Purpose: Radionuclide therapy directed against tumors that express somatostatin receptors (SSTRs) has proven effective for the treatment of advanced, low- to intermediate-grade neuroendocrine tumors in the clinic. In clinical usage, somatostatin peptide-based analogs, labeled with therapeutic radionuclides, provide an overall response rate of about 30%, despite the high cumulative activity injected per patient. We set out to improve the effectiveness of somatostatin radiotherapy by preparing a chemical analog … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
93
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 19 publications
1
93
1
Order By: Relevance
“…Animal hematology testing of complete blood counts from mice injected with IR‐12N3 at 24 h p.i. indicated the normal level of all measured blood cell subtypes compared with the reported healthy mice (Table S3, Supporting Information) . Pathology analysis by H&E staining indicated no morphological changes in all the tested organs (Figure S9, Supporting Information).…”
mentioning
confidence: 79%
“…Animal hematology testing of complete blood counts from mice injected with IR‐12N3 at 24 h p.i. indicated the normal level of all measured blood cell subtypes compared with the reported healthy mice (Table S3, Supporting Information) . Pathology analysis by H&E staining indicated no morphological changes in all the tested organs (Figure S9, Supporting Information).…”
mentioning
confidence: 79%
“…Time–activity curves (TACs) drawn over the tumors showed that radiolabeled Ag 2 Se@Mn@TATE in SSTR2 + tumor xenografts had much higher accumulation than both the control agent in SSTR2 + and Ag 2 Se@Mn@TATE in SSTR2 − tumors. The Ag 2 Se@Mn‐ 64 Cu@TATE reached 10%ID g −1 at 4 h time point in AR42J tumor (Figure b), which was comparable to that of radiolabeled DOTA‐TATE in the same tumor model . By contrast, Ag 2 Se@Mn‐ 64 Cu@TATE in SSTR2 − tumor mice and Ag 2 Se@Mn‐ 64 Cu in SSTR2 + tumor mice showed minimal uptake (≈2%ID g −1 at 4 h p.i.).…”
Section: Resultsmentioning
confidence: 61%
“…The body weight results were similar between the control and Ag 2 Se@Mn QDs treated groups (Figure S11, Supporting Information). At 24 h p.i., the animal blood samples were collected for hematology test and serum biochemistry analysis, and all the percentages of cell subgroups and serum biochemistry levels were in the normal range (Table S2, Supporting Information) . Pathology analysis by hematoxylin and eosin (H&E) staining indicated no morphological changes in all the tested organs (Figure S12, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Theranostics, Chen and colleagues reported the use of an Evans blue analog (EB) for albumin hitchhiking to improve both the PET imaging performance and therapeutic efficacy of radiolabeled TATE in several animal tumor models, targeting SSTR2 5 . Both the imaging and therapy results in these animal tumor models are very exciting, which could have significant clinical impact in the near future, once they are translated into the clinic.…”
mentioning
confidence: 99%